Solve the equation and express each solution in the form of A + Bi
2x^2-6X+3=0
Dear victorfk06,
$\displaystyle 2x^2-6x+3=0$
$\displaystyle x^2-3x+\frac{3}{2}=0$ (divide the whole equation by 2)
$\displaystyle \left(x-\frac{3}{2}\right)^2-\frac{9}{4}+\frac{3}{2}=0$
$\displaystyle \left(x-\frac{3}{2}\right)^2-\frac{3}{4}=0$
$\displaystyle x-\frac{3}{2}= \pm{\frac{\sqrt{3}}{2}}$
Therefore, $\displaystyle x = \frac{\sqrt{3}+3}{2}$ or $\displaystyle x = \frac{-\sqrt{3}+3}{2}$
This equation has real roots. So it is not necesary to express it in the form A+Bi.
Hope this helps.